How do Hospitals Respond to Price Changes? Evidence from Norway. (30th April 2015) - Januleviciute, Jurgita; Askildsen, Jan Erik; Kaarboe, Oddvar; Siciliani, Luigi; Sutton, Matt
Abstract: Many publicly funded health systems use activity‐based financing to increase hospital production and efficiency. The aim of this study is to investigate whether price changes for different treatments affect the number of patients treated and the mix of activity provided by hospitals. We exploit the variations in prices created by the changes in the national average treatment cost per diagnosis‐related group (DRG) offered to Norwegian hospitals over a period of 5 years (2003–2007). We use the data from Norwegian Patient Register, containing individual‐level information on age, gender, type of treatment, diagnosis, number of co‐morbidities and the national average treatment costs per DRG. We employ fixed‐effect models to examine the changes in the number of patients treated within the DRGs over time. The results suggest that a 10% increase in price leads to about 0.8–1.3% increase in the number of patients treated for DRGs, which are medical (for both emergency and elective patients). In contrast, we find no price effect for DRGs that are surgical (for both emergency and elective patients). Moreover, we find evidence of upcoding. A 10% increase in the ratio of prices between patients with and without complications increases the proportion of patients coded with complications by 0.3–0.4 percentage points. Copyright © 2015 John Wiley & Sons, Ltd.